Barriers and pathways to informed consent for ionising radiation imaging examinations: A qualitative study. Issue 4 (November 2019) - Younger, C.W.E.; Moran, S.; Douglas, C.; Warren-Forward, H.
Abstract: Introduction: Informed consent for ionising radiation medical imaging examinations represents a recent change to medical imaging practice. This practice has not had a definitive and authoritative integration into clinical practice, and lack of direction has caused many health care professionals to be unsure of an appropriate consent methodology. Consent practices have been undertaken inconsistently and sometimes poorly. This research sought to investigate what barriers exist to meaningful informed consent, and what pathways are suggested to overcome these barriers. These views are then discussed in the context of practical health care consent practices. Methods: A semi-structured interview explored the views of radiographers and radiologists on the practice of disclosing the ionising radiation risk of a clinical medical imaging examination. Qualitative data was analysed using a nominal method of quantitative transformation. Responses were reviewed, and a set of definitive themes constructed. Participants considered the influences, logistics and barriers to the informed consent process. Participants were then asked what pathways might be developed that would improve the process. Results: Twenty-one (21) radiographer participants and nine (9) radiologists were interviewed. The barriers to consent identified issues of time constraints, lack of a unified message, and patient presentations. Pathways suggested included limiting the scope of the consent practice, sharing the consent responsibility, and formulation of definitive consent guidelines. Conclusion: A unified, definitive series of guidelines for informed consent for ionising radiation examinations would alleviate many of the identified barriers. Having the consent process consistently begin with the referring doctor would facilitate more meaningful consent. Highlights: Ionising radiation risk disclosure is currently often undertaken inconsistently and poorly. Barriers to risk disclosure include time management and inconsistency of risk information. Radiographers and radiologists agree that a unified, authoritative risk document is needed. Limiting risk disclosure to higher-dose examinations may greatly reduce time commitments. Having informed consent consistently beginning with the referrer could improve patient care.